INFORMAL DIALOGUE WITH PROSPECTIVE VOLUNTEERS: A TOOL TO IMPROVE SUBJECT RECRUITMENT IN CLINICAL TRIALS - Ruckmani.A; ARUNKUMAR.R; LAKSHMIPATHY PRABHU.R; RAMYA.N; MAIGNANA KUMAR.R (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Background: Providing adequate information plays a key role in subject recruitment to clinical trials. Consent of the subjects to get recruited to clinical trials is usually taken in an official environment which could affect decision making. If consent is taken informally through a friendly chat whether it will influence the decision is not known and this study aims to find out the role of informal dialogue in taking a decision to participate in clinical trial.Â Objective: To find out the impact of informal dialogue on the willingness to participate in clinical trials. Methodology: The awareness, previous participation and willingness to participate in clinical trials were recorded randomly from the patients’ relatives who attended Chettinad hospital & Research institute. The participants who responded negatively were selected with their consent and given a leaflet containing information about clinical trials. Sufficient time was given for them to read the leaflet and clarify doubts. Their willingness to participate in clinical trial was recorded. Then they were individually met and explained about the clinical trials outside the official environment. Willingness to participate in clinical trials was recorded then and the difference between before and after personal interaction was statistically analyzed. Results: 200 subjects (99-males, 101-females) participated in this study. Before informal dialogue, 188 subjects (94%) were unwilling to participate and 12 (6%) expressed their willingness. After personal dialogue 137 (68.5%) were ready to participate and 63 (31.5%) were still unwilling to participate. The data was analyzed using Fisher’s exact test that showed that informal dialogue significantly improved the willingness to participate in clinical trials Conclusion: Informal dialogue outside the formal official environment has positively influenced the decision to take part in clinical trials. Keywords: Clinical trials, Willingness, Informal dialogue